34 ANALISIS KELAYAKAN USAHA KOPI LUWAK DI KECAMATAN BALIK BUKIT KABUPATEN LAMPUNG BARAT PROPINSI LAMPUNG (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
Feasibility Analysis of Kopi Luwak in District Balik Bukit West Lampung Regency of Lampung Province (guided by Dr. Munajat, S.P., M.Si and Fifian Permata Sari, S.P., M.Si). The purpose of this study is to Feasibility Kopi Luwak in District Balik Bukit West Lampung Regency of Lampung Province. This research has been conducted in the district Balik Bukit West Lampung Regency of Lampung Province. The location determination is done intentionally (purposive), with the consideration that the District is the center of civet coffee business in West Lampung Regency of Lampung Province. The sampling method used in the study is the method of saturated samples. The sheer number of samples taken from all the population of 15 players in the industry who manage civet coffee in the District Balik Bukit West Lampung Regency of Lampung Province. Based on the research effort civet coffee gained 1.54 results in accordance with the criteria of the existing provisions on equality R / C that R / C > 1 means that civet coffee business feasible to be developed or civet coffee favorable for entrepreneurs in Sub Balik Bukit Lampung Barat.